ANOTHER PERSPECTIVE OF QUALITY DIMENSIONS IN EDUCATION - Sukirno Sukirno (Jurnal Pendidikan Akuntansi Indonesia, 2008)
Like any other businesses, education needs quality. In the name of quality interest an organization is guaranteed be able to improve the effectiveness, efficiency, cohesiveness, flexibility, and competitiveness of its business as a whole. In the last few years there have been ever-increasing efforts devoted to the evaluation of quality and standards in education and other public services. Quality in education may even be more difficult to define than in most other sectors. In the past decade, following rapid economic development, the education systems of most countries or areas in the Asia-Pacific region have been expanded quickly. Currently, the people in this region are concerned with not only education quantity but also education quality. The indicators of education quality are often the satisfaction of students, teachers, parents, administrators, the education authority, the management committee, alumni, et cetera. This article gives another perspective of measuring educational management quality. Key Words : education quality